2012
DOI: 10.1007/s13142-012-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

Medication-taking beliefs and diabetes in American Samoa: a qualitative inquiry

Abstract: In American Samoa (AS), nearly 22% of adults have type 2 diabetes. Diabetes is best managed by diet and lifestyle modifications and strict medication adherence. Cultural aspects might affect medication-taking beliefs, and thereby influence medication adherence. This study aims to explore diabetes medication-taking experiences and knowledge and related cultural beliefs in AS adults with diabetes and healthcare providers. Six focus groups were conducted with 39 AS adults with diabetes and individual interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“… suggested participants needed non‐judgemental guidance on missed doses but felt unable to discuss adherence choices with providers. The acceptance of provider instructions was linked to cultural beliefs in one study, as evidenced by an American Samoan patient's view that, ‘What the doctor tells us is the same as what the Bible tells us, “No to this” and “Yes to this” and “No to that”—it's the same thing.’ .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… suggested participants needed non‐judgemental guidance on missed doses but felt unable to discuss adherence choices with providers. The acceptance of provider instructions was linked to cultural beliefs in one study, as evidenced by an American Samoan patient's view that, ‘What the doctor tells us is the same as what the Bible tells us, “No to this” and “Yes to this” and “No to that”—it's the same thing.’ .…”
Section: Resultsmentioning
confidence: 99%
“…Database searches identified 805 unique citations. Seven met the inclusion criteria [16,17,20,[22][23][24][25] and an eighth study [26] was identified from forward searching of included studies. Some studies were excluded at full-text stage that met most of the inclusion criteria but which we judged did not have a primary focus on the experience of taking oral medication (e.g.…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations